The impacts of Seri Tanjung Pinang Coastal reclamation on the quality of life of the Tanjung Tokong Community Penang, Malaysia - Mohd Nadzir, Nadzhirah; Ibrahim, Mansor; Mansor, Mazlina (Global Institute of Science & Technology, 2015)
The alteration of coastal would change the environment, thus severely affect local community’s quality of life. This paper presents the impacts of coastal reclamation on the quality of life of the local community in the study area. The results show that three main variables - flash flood, traffic congestion and health, influenced the quality of life of the community in the affected area. It is recommended that the coastal reclamation process on the approval part should consider any temporary and permanent negative impact to the local community.